Hubungan Determinasi Diri dengan Pengambilan Keputusan Karir Siswa Kelas XI MAN 2 Kota Bogor - Imam Sanusi; Putri Ria Angelina; Reni Sinta Dewi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Career selection is one of the important developmental tasks during adolescence, but many students still experience difficulties in determining further education and career choices that suit their potential. Low career decision-making ability can be influenced by various factors, one of which is self-determination. This study aims to analyze the relationship between self-determination and career decision-making in grade XI students of MAN 2 Bogor City. The study used a quantitative approach with a correlational design. The study population was 174 students, while a sample of 121 students was determined using a random sampling technique. Data were collected using a self-determination scale adapted from the Basic Psychological Needs Scale and a career decision-making scale, then analyzed using a correlation test. The results showed that the level of self-determination of students was in the moderate category (71.1%), as was the level of career decision-making (67.9%). The analysis showed a significant positive relationship with a strong relationship strength between self-determination and career decision-making. This finding indicates that the higher the self-determination of students, the better their ability to make career decisions. Therefore, strengthening self-determination needs to be a concern in guidance and counseling services to help students plan their careers more maturely.